John Dewey : la démocratie comme forme de vie et ses implications éducatives. - Michel Fabre (Éducation et Socialisation)
The topic of Democracy is one of the main threads of Dewey's thought. It receives three fundamental meanings from him. It designates a political regime, but also a way of life and even more fundamentally, it is confused with education as self-contrôle. How do these three senses fit together? And what is the impact of these conceptions on democracy at school? Wesbroock's hypothesis in John Dewey and American Democracy (1991), is that Dewey, upon leaving the University of Chicago, would have gradually turned away from pedagogical reflection on democracy in education in favor of a broader political reflection on the relationships between democracy and education. Hence the impression of a “missing link” between philosophy of education and concrete pedagogical reflection. This article tests these hypotheses by comparing the philosophical and educational writings of the Later Works of the years 1930-1953 and those of the Middle Works of the years 1910-1920. It highlights the continuity of a philosophical and educational reflection on democracy at school, but which, in last t remains, in the last period, at the level of principles, without addressing its concrete implementation.